Ion-exchanged LTA zeolite derived nepheline phase NaAlSiO4:Eu2+ ceramic phosphor for laser illumination. Issue 21 (1st November 2021) - Fan, Yuxiao; Lin, Hui; Liu, Hongwei; Zhang, Linjing; Wang, Jiaying; Xie, Qi; Zhou, Li; Hong, Ruijin; Zhang, Dawei; Tian, Yanna; Chen, Jie; Zhou, Shengming
Abstract: A reliable yellow phosphor converter that can be efficiently excited by a 405 nm bluish violet laser is in high demand for laser illumination applications. A NaAlSiO4 :Eu 2+ phosphor with a quantum efficiency reaching 92% was obtained using LTA zeolite as the raw material. NaAlSiO4 :Eu 2+ ceramics with suitable porosities for laser illumination were prepared from the phosphor powders via spark plasma sintering. The ceramics lost only 2% of the quantum efficiency compared to the powders, maintained good thermal quenching properties (30% drop at 150 °C), and showed good thermal conductivity (2.02 W‧m −1 ‧K −1 ). The NaAlSiO4 :Eu 2+ ceramic with 405 nm bluish violet lasers, with the increase in laser power density to 9.15 W/mm 2, exhibited an increasing luminous flux (23.83–70.26 lm) and maintained a stable luminous efficacy (47.7–46.8 lm/W), and the temperature distribution of the ceramic remained uniform and stable under long-time laser irradiation. This indicates that the nepheline-phase NaAlSiO4 :Eu 2+ ceramic is a promising material for laser illumination.